Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires